Antivaccine Movement and COVID-19 Negationism: A Content Analysis of Spanish-Written Messages on Twitter - Herrera Peco, Ivan; Jiménez Gómez, Beatriz; Romero Magdalena, Carlos Santiago; Peña Deudero, Juan José; García Puente, María; Benitez de Gracia, Elvira; Ruiz Núñez, Carlos (My University, 2021)
During the COVID-19 pandemic, different conspiracies have risen, with the most dangerous being those focusing on vaccines. Today, there exists a social media movement focused on destroying the credibility of vaccines and trying to convince people to ignore the advice of governments and health organizations on vaccination. Our aim was to analyze a COVID-19 antivaccination message campaign on Twitter that uses Spanish as the main language, to find the key elements in their communication strategy. Twitter data were retrieved from 14 to 28 December using NodeXL software. We analyzed tweets in Spanish, focusing on influential users, most influential tweets, and content analysis of tweets. The results revealed ordinary citizens who ¿offer the truth¿ as the most important profile in this network. The content analysis showed antivaccine tweets (31.05%) as the most frequent. The analysis of anti-COVID19 tweets showed that attacks against vaccine safety were the most important (79.87%) but we detected a new kind of message presenting the vaccine as a means of manipulating the human genetic code (8.1%). We concluded that the antivaccine movement and its tenets have great influence in the COVID-19 negationist movement. We observed a new topic in COVID-19 vaccine hoaxes that must be considered in our fight against misinformation. Keywords: COVID-19; fake news; misinformation; public health; Twitter; vaccines